2020
DOI: 10.4097/kja.19360
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular blockade reversal with sugammadex versus pyridostigmine/glycopyrrolate in laparoscopic cholecystectomy: a randomized trial of effects on postoperative gastrointestinal motility

Abstract: Background: Acetylcholinesterase inhibitors (e.g., pyridostigmine bromide) are used for neuromuscular blockade (NMB) reversal in patients undergoing surgery under general anesthesia (GA). Concurrent use of anticholinergic agents (e.g., glycopyrrolate) decreases cholinergic side effects but can impede bowel movements. Sugammadex has no cholinergic effects; its use modifies recovery of gastrointestinal (GI) motility following laparoscopic cholecystectomy compared to pyridostigmine/glycopyrrolate. This study eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…In intraperitoneal surgery, sugammadex does seem to accelerate bowel movement [10,11], but in nonintraperitoneal surgery, such as thyroidectomy, sugammadex and neostigmine/glycopyrrolate did not show signi cant differences in bowel movement. The difference between intraperitoneal and nonintraperitoneal surgery consists in the manipulation of the bowel during surgery.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In intraperitoneal surgery, sugammadex does seem to accelerate bowel movement [10,11], but in nonintraperitoneal surgery, such as thyroidectomy, sugammadex and neostigmine/glycopyrrolate did not show signi cant differences in bowel movement. The difference between intraperitoneal and nonintraperitoneal surgery consists in the manipulation of the bowel during surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Previous comparative reports regarding postoperative bowel function following the administration of sugammadex or neostigmine are limited to two randomized controlled trials and one retrospective study [9][10][11]. Sen et al [9] did not nd a signi cant difference in the time to rst atus between sugammadex…”
Section: Discussionmentioning
confidence: 97%
“…Most of these studies compare neostigmine against sugammadex, a selective rocuronium or vecuronium binder, with varied results. Sugammadex has affinity to bind with steroid hormones, thus it is thought to theoretically increase gastric emptying and gut motility 42 . Sen et al .…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“… 91 Sugammadex administration against profound blockade in laparoscopic cholecystectomy or appendectomy had positive effects on the recovery of gastrointestinal motility compared with the use of a mixture of glycopyrrolate and pyridostigmine. 92 Concerning patients who underwent laparoscopic hysterectomy, a series of randomized controlled trials have proved the superiority of sugammadex administration in effectively reversing deep block at the end of the procedure and shortening the length of hospital stay. 93 , 94 Many studies showed that the robotic approach had longer operative time compared with conventional laparoscopic surgery.…”
Section: The Effect Of Sugammadex On Deep Neuromuscular Blockade Used For Various Laparoscopic Surgeriesmentioning
confidence: 99%